The spatiotemporal characteristics of the C1 component and its modulation by attention. Issue 1 (3rd April 2018) - Mohr, Kieran S.; Kelly, Simon P.
ABSTRACT: Slotnick (this issue) provided a selective review of studies on the attentional modulation of the C1 component of the visual evoked potential, and offers a number of guidelines to maximize the likelihood of observing such modulation in terms of electrode choice, stimulus placement, and types of attentional cue and target stimulus. However, the broader literature pertaining to attentional modulation of the C1 does not support many of these guidelines, and the question of why exactly C1 modulations are so rare remains very much open. Here, we provide clarifications that are critical to an accurate appraisal of the current state of this literature.